1997
DOI: 10.1023/a:1024856613829
|View full text |Cite
|
Sign up to set email alerts
|

Effect of blameworthiness and outcome severity on attributions of responsibility and damage awards in comparative negligence cases.

Abstract: We studied the effects of accident victims' legal blameworthiness and the severity of their injuries on determinations of responsibility and damage awards. In general, participants tended to ascribe more fault to victims than warranted by the facts presented, displaying an antiplaintiff bias. When attributing fault and awarding damages, they were especially sensitive to the blameworthiness of the victim when the consequences of the accident were severe rather than mild. These findings appeared not to be mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
68
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 42 publications
9
68
2
Order By: Relevance
“…Juries are instructed to do two separate things; first they determine the responsibility of both the defendant and the plaintiff (the injured party), and then they estimate the total damage to the plaintiff, knowing that the court will reduce the ultimate award to the plaintiff below total damage if the jury found the plaintiff to be partly responsible for the injury. However, studies have found that juries' estimates of total damage are inversely related to the degree to which the plaintiff was considered responsible (e.g., Feigenson, Park, & Salovey, 1997;Zickafoose & Bornstein, 1999). Even though specifically instructed to determine the gross amount of damages incurred by the plaintiff without regard to the plaintiff's degree of negligence, jurors' estimates reflected in part their assessments of negligence.…”
mentioning
confidence: 99%
“…Juries are instructed to do two separate things; first they determine the responsibility of both the defendant and the plaintiff (the injured party), and then they estimate the total damage to the plaintiff, knowing that the court will reduce the ultimate award to the plaintiff below total damage if the jury found the plaintiff to be partly responsible for the injury. However, studies have found that juries' estimates of total damage are inversely related to the degree to which the plaintiff was considered responsible (e.g., Feigenson, Park, & Salovey, 1997;Zickafoose & Bornstein, 1999). Even though specifically instructed to determine the gross amount of damages incurred by the plaintiff without regard to the plaintiff's degree of negligence, jurors' estimates reflected in part their assessments of negligence.…”
mentioning
confidence: 99%
“…Hence, they found at least an indirect relationship between the level of comparative negligence and the amount of the damage award, but the reductions in the amounts of the awards were not directly proportional to the plaintiff's level of negligence as determined by the participants. Feigenson, Park, and Salovey (1997) manipulated the blameworthiness of the victim and the severity of the accident across four different case summaries. Participants estimated the fault for both the plaintiff and defendant, determined a gross damage award, and then determined an adjusted damage award that was discounted by the percentage of fault attributed to the plaintiff.…”
Section: Introductionmentioning
confidence: 99%
“…When the plaintiff's injury was mild, the reprehensibility of the defendant's conduct increased compensatory damage awards but the reprehensibility of the defendant's conduct had no effect on compensatory damages when the plaintiff's injuries were severe (Greene et al, 2001). Compensatory damages were lower when jurors attributed more blame for the incident to the plaintiff than when they thought that the plaintiff was less at fault for his or her injuries (Feigenson et al, 1997). The amount of blame attributed by jurors to the plaintiff mattered when jurors perceived the plaintiff's injuries to be severe than when they believed the injuries were mild (Feigenson et al, 1997).…”
Section: Hart Morry and Saks 1997) Research Into How Jurors Award Cmentioning
confidence: 92%
“…Compensatory damages were lower when jurors attributed more blame for the incident to the plaintiff than when they thought that the plaintiff was less at fault for his or her injuries (Feigenson et al, 1997). The amount of blame attributed by jurors to the plaintiff mattered when jurors perceived the plaintiff's injuries to be severe than when they believed the injuries were mild (Feigenson et al, 1997).…”
Section: Hart Morry and Saks 1997) Research Into How Jurors Award Cmentioning
confidence: 92%
See 1 more Smart Citation